Small and medium company valuation by discounted cash flow: philosophical and epistemological basis - Boza Pró, Germán Alfredo (2020)
The majority of experts recognizes the cash flow discount as the best technique to value SMEs. However, there is a divergence in the concepts and criteria that a valuation model must incorporate. neoclassical finance, heiress of logical positivism as an epistemological basis, maintains the efficient market hypothesis (EMH) y the capital asset pricing model (CAPM), to calculate the discount rate. On the contrary, behavioral finance, heiress of Husserl's phenomenology, suggests incorporating human behavior or behavior into its valuation models. On taking position, on one way or another, from a philosophical point of view, a valuation model, should lead us to the encounter of truth, justice and fairness in decision making. Both aspects of company valuation, philosophical and epistemological, are addressed in the present research, analyzing the different theories and positions in force, ending with a final position regarding the 2 valuation models of companies currently existing within Neoclassical Finance: the Damodaran Model and the Fernández Model.